Profiling Critical Thinking and AI Attitudes in Management Education Using a Factor-Cluster Approach for the Digital Business Era - Saibaba, S. (Pandawan, 2026)
This paper investigates the relationship between critical thinking skills and attitudes toward artificial intelligence among postgraduate management students in southern India. Data were collected through an online survey from 325 postgraduate management students from various business schools in southern India. An empirical research design was used to identify four dimensions through exploratory factor analysis, Confidence in Critical Thinking, Valuing Critical Thinking, Misconceptions of Critical Thinking, and Attitudes Toward AI. These dimensions have guided the K-means clustering, grouping students into three distinct clusters, Critical Thinkers & AI Optimists, Developing Thinkers & AI Moderates, and Novice Thinkers & AI Skeptics. The findings reveal notable gender differences across the clusters and distinct demographic patterns that are valuable for tailoring education strategies. Overall, the results emphasize the important role of both critical thinking and AI literacy in preparing management students for success in the digital business era. This study will contribute to the theoretical understanding of these dynamics while providing practical recommendations for better curriculum design in management education that equips students with cognitive and technological skills required to navigate complex, technology-driven business environments.